L'adresse à Dieu schermo del sé (Mantichora. Italian Journal of Performance Studies, 2020)
The texts which this study refers to form part of a particular epistolary anthology with multiple senders, but with only one declared addresse, God,commissioned to various intellectuals by the theologist René Guitton. Within the epistolary genre – a performative space, in that it is the place for the performance of the self and the other – the particularity of the pragmatic-communicative relationship that binds the real sender to an imaginary addresse and, as such, inadequate to put into action the expected mechanism of feed- back, will be examined. To this end, the comunicative circumstance of such an act of writing, that is what concerns the bifurication of the destination of these special epistolary acts, will be taken into consideration. One destination is that directed towards the external readers of the volume of letters that the editor-client will publish; the other destination is that created by the movement of the division of the I into a Me, the only feasible otherness to whom one addresses one’s own performance in an auto- reflective movement.